Neural control of food intake and energy balance - Berthoud, Hans-Rudolf (Henry Stewart Talks, 2007)
Sensing nutrients in the alimentary canal, Sensing absorbed nutrients, Hindbrain control of meal size, Hypothalamic control of energy balance, Environmental influences on body weight regulation, Cognitive controls of food intake, Food as reward